저항전분 함유 도담쌀 볶음 현미가루의 입도별 품질특성 - 박지영(Jiyoung Park); 이석기(Seuk-Ki Lee); 최인덕(Induck Choi); 최혜선(Hye-Sun Choi); 김남걸(Namgeol Kim); 신동선(Dong Sun Shin); 정광호(Kwang-Ho Jeong); 박장환(Chang-hwan Park); 정현정(Hyun-Jung Chung); 오세관(Sea-kwan Oh) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2019)
In this study, the general components, particle size, starch content, hydrolysis index (HI), and estimated glycemic index (eGI) of 'Ilpum', a medium-amylose rice cultivar, were compared with those of 'Dodamssal', a high-amylose rice cultivar containing resistant starch. The volume weighted mean was significantly smaller in 'Dodamssal' than in 'Ilpum'. The resistant starch content of 'Dodamssal' was about 13% and there were no differences in terms of particle size. The HI and eGI were found to be significantly higher in 'Ilpum', and there were no statistical differences in 'Dodamssal' except for samples with an average particle size of less than 50 ㎛. Therefore, 'Dodamssal' was concluded to be valuable as a health-food material since it is easily ground evenly when processed into rice flour, contains resistant starch, and has a low glycemic index. These results could be used as basic data for developing processed 'Dodamssal' rice-based products.